Perubahan Putusan Lepas Menjadi Putusan Pemidanaan oleh Judex Juris Terhadap Putusan Tingkat Pertama - Arifin, Alfredo Juniotama; Adhari, Ade (UNES Law Review, 2023)
This study aims to examine the Supreme Court decision number 2113 K/Pid.Sus/2023 related to the money laundering case of Indosurya Cipta Savings and Loan Cooperative for the defendant Henry Surya. In the Supreme Court decision, the judex juris overturned the decision of the district court that released the defendant from all charges. West Jakarta District Court Decision Number 779/Pid.B/2022/PN Jkt.Brt stated that the charges were proven, but the alleged actions could not be categorized as a criminal offense. The Panel of Judges erred in handing down a decision, after which the Public Prosecutor filed a cassation appeal on the grounds that the Judex Facti did not apply the law correctly and properly. This research uses a normative legal research method with a case approach as the main approach to explore and analyze relevant legal aspects. This approach allows researchers to understand and assess legal norms related to the case under study. Based on the results of the research, it shows that the basis for filing a cassation by the Public Prosecutor related to the money laundering crime case is that the judex facti did not apply the law correctly in accordance with the provisions of Article 253 of the Criminal Procedure Code. This case involves the overturning of the sentence by the judex juris because the judex facti is considered to have erred in the implementation of the law by ignoring the legal facts revealed in the trial process due to the lack of conformity between the facts and the evidence.